2011
DOI: 10.1016/j.ejcts.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Radial artery versus saphenous vein conduits for coronary artery bypass surgery: forty years of competition — which conduit offers better patency? A systematic review and meta-analysis

Abstract: The internal thoracic artery is the most effective conduit for coronary artery bypass surgery; however, most patients have multivessel disease and require additional saphenous vein or radial artery grafts. In this systematic review of the literature and meta-analysis, we aim to compare reported patency rates for these conduits and explore if differences are homogeneous across follow-up intervals. A literature search was performed using Embase, Medline, Cochrane Library, Google Scholar and randomised controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 54 publications
0
73
0
3
Order By: Relevance
“…В двух рандомизиро-ванных исследованиях проходимость шунта из луче-вой артерии через 1 год была неодинаковой -как "превосходной", так и "эквивалентной" венозным шунтам [414,415]. В дополнительном небольшом рандомизированном исследовании 5-летняя прохо-димость шунта из лучевой артерии была достоверно лучше, чем венозных шунтов, если их соединяли с системой огибающей артерии [416,417].…”
Section: Iib B 373-375unclassified
“…В двух рандомизиро-ванных исследованиях проходимость шунта из луче-вой артерии через 1 год была неодинаковой -как "превосходной", так и "эквивалентной" венозным шунтам [414,415]. В дополнительном небольшом рандомизированном исследовании 5-летняя прохо-димость шунта из лучевой артерии была достоверно лучше, чем венозных шунтов, если их соединяли с системой огибающей артерии [416,417].…”
Section: Iib B 373-375unclassified
“…18 Early radial artery patency was similar to vein graft patency, medium-term follow-up demonstrated deterioration in vein graft patency, and radial artery patency was superior in long-term followup. The long-term radial artery patency ranged from 85% to 94.9% and the saphenous vein patency ranged from 64.5% to 91.7%; the pooled OR for 7 studies indicated better patency with the radial artery conduits.…”
Section: Longevity Of Patent Radial Graftsmentioning
confidence: 89%
“…The long-term radial artery patency ranged from 85% to 94.9% and the saphenous vein patency ranged from 64.5% to 91.7%; the pooled OR for 7 studies indicated better patency with the radial artery conduits. 18 The authors suggested a nonhomogeneous comparative patency of radial arteries and saphenous vein grafts over time and recommended preferential radial artery use over saphenous vein use for CABG conduit in all patients who have a life expectancy Ͼ5 years. This meta-analysis lends support for the durability of radial artery grafts after the initial postoperative period.…”
Section: Longevity Of Patent Radial Graftsmentioning
confidence: 99%
“…[2] [4] The use of SV was pioneered by Favaloro in early years of CABG [3] [4]. Studies shows that patients with hypertension, diabetes, peripheral vascular disease, aortic disease and stroke have higher risk for coronary artery disease especially in elderly patients [5].…”
Section: Discussionmentioning
confidence: 99%